A Study of Professional Ethics of Teachers in Higher Education - Harmeet Kaur; Prof. (Dr.) Rajnee Gaur (Educational Administration: Theory and Practice, 2023)
Professional ethics refers to the norms of morality, principles or guidelines a teacher should follow when dealing with students, parents, the community, the profession and the colleagues. The objective of the study was to find out the Professional Ethics of teachers teaching in higher educational institutes. A sample of 80 teachers from Ghaziabad districts was taken using random sampling technique. The investigator used descriptive survey method for the study. Data was analysed by calculating Mean, Standard Deviation and ‘t’ test. The findings of the study revealed that the teachers had moderate level of professional ethics. No significance difference was found in the Professional ethics of teachers in terms of gender. The study highlighted the importance of professional ethics of teachers to train the students by inculcating good qualities in them to become the responsible future citizens.